2023
DOI: 10.1007/s10803-023-06133-0
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Behaviours in Autistic and Non-Autistic Adults: Associations with Sensory Sensitivity and Impact on Self-Efficacy

Gabrielle Nwaordu,
Rebecca A. Charlton

Abstract: Purpose: Restricted and repetitive behaviours are a core feature of autism diagnoses but have not been widely studied in adulthood. This study examined the rates of and associations between repetitive behaviours and sensory sensitivity in autistic and non-autistic adults; and whether repetitive behaviours described as “stimming” impacted coping with difficulties (self-efficacy). Methods: Diagnosed autistic (n = 182), undiagnosed autistic (n = 163) and non-autistic (n = 146) adults completed online measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…A recent human study showed that reductions in repetitive behaviors in individuals are associated with an increase in other autism phenotypes like anxiety and social difficulties and vice versa, suggesting that some repetitive behaviors may be a self-regulation mechanism rather than a primary phenotype in autism 275 . Given the close correlations that have been found between repetitive behaviors and sensory sensitivity and the beneficial effects of repetitive behaviors 276 , our finding that sensory dysregulation is the more dominant brain phenotype in rsfMRI of MIR mice with SOR, supports the idea of an emergence of repetitive behaviors as coping mechanism rather than being a cause of dysfunction. The acute rapamycin treatment in MIR mice reduced FC towards control levels in the cortex but curiously caused even greater FC differences in subcortical structures.…”
Section: Discussionsupporting
confidence: 74%
“…A recent human study showed that reductions in repetitive behaviors in individuals are associated with an increase in other autism phenotypes like anxiety and social difficulties and vice versa, suggesting that some repetitive behaviors may be a self-regulation mechanism rather than a primary phenotype in autism 275 . Given the close correlations that have been found between repetitive behaviors and sensory sensitivity and the beneficial effects of repetitive behaviors 276 , our finding that sensory dysregulation is the more dominant brain phenotype in rsfMRI of MIR mice with SOR, supports the idea of an emergence of repetitive behaviors as coping mechanism rather than being a cause of dysfunction. The acute rapamycin treatment in MIR mice reduced FC towards control levels in the cortex but curiously caused even greater FC differences in subcortical structures.…”
Section: Discussionsupporting
confidence: 74%
“…More precisely, we hold that the propensity to tic within certain contexts serves to resolve ambiguity about the status of the inferred, agentive self by disambiguating the outcomes of self-generated action and worldly events (Clarke, 1996). This crucially involves both information gain about the agent 'that I am' and the fulfilment of a supervening pragmatic imperative, which draws me to act so that 'I will be able to observe the sensations that I cause'-perhaps the most overt expression of self-evidencing (see e.g., self-stimming behaviour in severe autism (Nwaordu & Charlton, 2023). This need to buttress my belief-about the type of thing that I am-stems from the failure of sensory attenuation outlined above.…”
Section: Section 2: Tics As Epistemic Foragingmentioning
confidence: 99%
“…In fact, we suggest that our four-tiered model may provide explanatory power beyond TS and OCD, especially since it is unclear to what degree tics (or at least tic-like movements) are exclusive to TS. Indeed, certain aspects of our model might be able to generate insights into the neurocognitive processes relevant to the expression of motoric phenomena that resemble tics within both hypo-and (especially) hyper-kinesias, including self-stimming in autism spectrum disorder ASD (Nwaordu & Charlton, 2023), but also stimulus utilisation behaviours (Janik et al, 2018), functional tics (Cavanna et al, 2023), and attention deficit hyperactivity disorder (ADHD). For example, in ASD, individuals may produce self-initiated (rhythmic) actions to regulate sensory input (e.g., to ameliorate symptoms of hypersensitivity), otherwise known as self-stimming.…”
Section: Empirical Predictions Limitations and Future Directionsmentioning
confidence: 99%
“…More precisely, we hold that the propensity to tic within certain contexts serves to resolve ambiguity about the status of the inferred, agentive self by disambiguating the outcomes of self-generated action and worldly events (Clarke, 1996). This crucially involves both information gain about the agent "that I am" and the fulfilment of a supervening pragmatic imperative, which draws me to act so that "I will be able to observe the sensations that I cause"-perhaps the most overt expression of self-evidencing (see e.g., selfstimming behaviour in severe autism (Nwaordu & Charlton, 2023). This need to buttress my belief-about the type of agent that I am-stems from the failure of sensory attenuation outlined above.…”
Section: Section 2: Tics As Epistemic Foragingmentioning
confidence: 99%
“…In fact, we suggest that our four-tiered model may provide explanatory power beyond TS and OCD, especially because it is unclear to what degree tics (or at least tic-like movements) are exclusive to TS. Indeed, certain aspects of our model might be able to generate insights into the neurocognitive processes relevant to the expression of motoric phenomena that resemble tics within both hypoand (especially) hyper-kinesias, including self-stimming in autism spectrum disorder ASD (Nwaordu & Charlton, 2023) but also stimulus utilisation behaviours (Janik et al, 2018), functional tics (Cavanna et al, 2023), and attention deficit hyperactivity disorder (ADHD). For example, in ASD, individuals may produce self-initiated (rhythmic) actions to regulate sensory input (e.g., to ameliorate symptoms of hypersensitivity), otherwise known as selfstimming.…”
Section: Empirical Predictions Limitations and Future Directionsmentioning
confidence: 99%